Research on monitoring the load of short-distance orienteering sports on campus based on embedded system acceleration sensor - Ren, Hua; Hu, Wenwu; Wang, Shan (Microprocessors and microsystems, 2021)
Orienteering means that competitors need to be identified, with a specific focus on the city on a predetermined terrain or with the help of a guide, in this game, which is predicted by the execution of time, their ability to integrate their actual perseverance with the mental cycles and adjust to the environment and regulate them effectively. Acceleration Sensors observe these decisions in the selected courses, and each course has its environmental characteristics. Subsequently, competitors must disassemble these features well and choose the course that campus-based embedded system. In the short distance, orienteering sports components that affect course selection will be examined. For this reason, competitor's information is obtained by having watched an orienteering race organized by the Federation. The information collected verified through quantitative and subjective strategies, and an overall understanding of competitors 'behavior obtained and qualification of moldable and subject-subordinate components in competitors' dynamics. From the model able parts, a model created that recorded the separation and the brief separation based on the landscape surface and, subsequently, analyzed its similarity with the competitors' practices. Moreover, the results were justified by different factual observations. According to Data Pathway Algorithm, the effects of the investigation, environmental factors play a significant role in competitors' dynamics. The model implementation is much more accurate in short-segmented courses than insignificant distance courses that reduce the psychological burden.